2013
DOI: 10.1111/1477-8947.12007
|View full text |Cite
|
Sign up to set email alerts
|

The economic impacts of tourism in Botswana, Namibia and South Africa: Is poverty subsiding?

Abstract: Tourism in southern Africa is based on the region's wildlife and nature assets and is generally environmentally sustainable, but the extent to which it contributes to other aspects of sustainable development — overall income generation or poverty eradication — is less well explored. In this paper, we use social accounting matrices to compare the economic impacts of foreign tourism in Botswana, Namibia and South Africa. Overall impacts on GDP range from 6% (South Africa) to 9% (Namibia). However, South Africa's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Empirical studies on the effects of tourism on the poor have been conducted using two approaches, namely, simulation and econometrics (Kim, Song, and Pyun 2016). Studies that make use of the simulation approach includes Blake et al (2008) for Brazil; Wattanakuljarus and Coxhead (2008) for Thailand; Saayman, Rossouw, and Krugell (2012) for South Africa; Muchapondwa and Stage (2013) for Botswana, South Africa, and Namibia; Croes and Rivera (2017) for Ecuador; and Njoya and Seetaram (2018) for Kenya. 3 At the other end, the econometric studies include Croes and Vanegas (2008) for Nicaragua; Croes (2014) and Vanegas, Gartner, and Senauer (2015) for Nicaragua and Costa Rica; Kim, Song, and Pyun (2016) for 69 developing countries; and Mahadevan and Suardi (2017) focused on 13 tourism-intensive economies.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies on the effects of tourism on the poor have been conducted using two approaches, namely, simulation and econometrics (Kim, Song, and Pyun 2016). Studies that make use of the simulation approach includes Blake et al (2008) for Brazil; Wattanakuljarus and Coxhead (2008) for Thailand; Saayman, Rossouw, and Krugell (2012) for South Africa; Muchapondwa and Stage (2013) for Botswana, South Africa, and Namibia; Croes and Rivera (2017) for Ecuador; and Njoya and Seetaram (2018) for Kenya. 3 At the other end, the econometric studies include Croes and Vanegas (2008) for Nicaragua; Croes (2014) and Vanegas, Gartner, and Senauer (2015) for Nicaragua and Costa Rica; Kim, Song, and Pyun (2016) for 69 developing countries; and Mahadevan and Suardi (2017) focused on 13 tourism-intensive economies.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Based on the findings by Akinboade and Braimoh (2010), it could be inferred that tourism helps the poor. In addition, Muchapondwa and Stage (2013) used data for three Southern African countries—Botswana, Namibia and South Africa. They analyzed the data using social accounting matrices and found that in the selected countries, the poor segment of the population benefited the least from tourism development.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…There is a widely accepted relationship between the value of multiplier effect and the level of economic development (Zhang, Madsen and Jensen-Butler, 2007;Yang, Fik and Altschuler, 2018), the more developed regions being able to display higher values of multiplier effects. Additional studies proved that the multiplier effect can be positively influenced by the level of national or regional economic diversification (Muchapondwa and Stage, 2013), due to the chances of involving more sectors of economy, the level of infrastructure (Freeman and Sultan, 1997;Huse, Gustavsen and Almedal, 1998), the number of inhabitants (van Leeuwen, Nijkamp and Rietveld, 2009) or the typology of tourist attractions (for example van Leeuwen, Nijkamp and Rietveld, (2009) found that the coastal destinations where the sun is the main resource tend to have a larger multiplier effect, while the destinations based on cultural resources recorded the lowest values of multiplier effect). Hansen and Jensen (1996) suggested that a richer region dominated by 3+ stars hotels tends to express a higher multiplier effect than a poorer region dominated by 2 stars' hotels or camping, while Ntibanyurwa (2006) offered evidence for a higher multiplier effect on the regions with small businesses.…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%
“…Globally, wildlife remains significant to many peoples’ for subsistence (Wenzel ; Nuttall et al ; Fa et al. ), income (Child ; Murphree ; Muchapondwa & Stage ), and cultural purposes (Bullock ; Wagner et al. ; Triezenberg et al.…”
Section: Introductionmentioning
confidence: 99%